Pluriactivity on family farms - Marta Błąd (Wieś i Rolnictwo)
The article elaborates on pluriactivity, i.e. taking non-agricultural jobs by farm household members. According to the research, pluriactivity is a universal phenomenon which can be observed in any country, regardless of its development level. It exists on large as well as small farms, although it is of more economic importance for those living on the latter. Pluriactivity is a response to a global concern known as the agrarian question, which is related chiefly with agricultural income disparity. Pluriactivity is a common and relatively stable phenomenon concerning a significant group of farmers. These facts are a cue for policy makers who should make non-agricultural job creation a part of rural development support programmes.